The biological activities and phytochemical content of Ferulago humulis Boiss - (:unkn) unknown (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2020)
Ferulago humulis Boiss. is an endemic species growing in Turkey. The aim of the study was to compare in vitro antioxidant and antimicrobial activities of the aerial parts (HFH) and rhizomes (RFH) of F. humulis. According to the results of antimicrobial and antioxidant activities of the extracts obtained from different parts of the plant, their phytochemical contents were evaluated. Petroleum ether (HFH-PE; RFH-PE), dichloromethane (HFH-DM; RFH-DM) and methanol (HFH-ME; RHI-ME) extracts from aerial parts (HFH) and rhizomes (RFH) of F. humulis were obtained for antimicrobial activity and examined by the agar hole diffusion and microdilution methods. Chromatographic and spectroscopic (H-1 NMR, LS-MS and UV) techniques were used for the isolation of coumarin compounds from petroleum ether (RFH-PE) and dichloromethane (RFH-DM) extracts. Furthermore, antioxidant activity were assayed by the 4 different methods in methanol extracts (HFH-ME; RFH-ME). HFH-PE (MIC=6.25 mg/mL), RFH-PE (MIC=12.5 mg/mL) and RFH-DM (MIC=11 mg/mL) extracts against Staphylococcus aureus, and RFH-PE (MIC= 3.125 mg/mL), HFH-PE (MIC=6.25 mg/mL) extracts showed antimicrobial activity against S. epidermidis. HFH-PE (MIC=1.56 mg/mL), RFH-PE (MIC= 6.25 mg/mL) extracts exhibited antifungal activity against Candida tropicalis. From the rhizomes of F. humulis isoimpemtorin, bergapten, oxypeucedanin, mamiesin senecioate and oxypeucedanin hydrate known as furanocoumarins derivatives were isolated.
Keywords: Antimicrobial activity; Antioxidant activity; Ferulago humulis; Isolation coumarin; ANTIOXIDANT PROPERTIES; TRACHYCARPA-BOISS.; ESSENTIAL OIL; COUMARINS; ROOTS